2014
DOI: 10.1097/shk.0000000000000253
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Derived Chemokine (CCL22) Is a Novel Mediator of Lung Inflammation Following Hemorrhage and Resuscitation

Abstract: Resuscitation of patients after hemorrhage often results in pulmonary inflammation and places them at risk for the development of acute respiratory distress syndrome. Our previous data indicate that macrophage-derived chemokine (MDC/CCL22) is elevated after resuscitation, but its direct role in this inflammatory response is unknown. MDC signaling through the C-C chemokine receptor type 4 (CCR4) is implicated in other pulmonary proinflammatory conditions, leading us to hypothesize that MDC may also play a role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 29 publications
2
31
0
Order By: Relevance
“…It was downregulated in DOCK8 patients when compared to Ctrls (Figure D). MDC was shown to be involved in various immune responses and elimination of pathogens, allergic reactions, and inflammation in the lungs . Hence, upregulation of MDC (Figure E) is consistent with the clinical features (infections, allergies, and pneumonia) seen in the DOCK8‐deficient patients.…”
Section: Discussionsupporting
confidence: 68%
“…It was downregulated in DOCK8 patients when compared to Ctrls (Figure D). MDC was shown to be involved in various immune responses and elimination of pathogens, allergic reactions, and inflammation in the lungs . Hence, upregulation of MDC (Figure E) is consistent with the clinical features (infections, allergies, and pneumonia) seen in the DOCK8‐deficient patients.…”
Section: Discussionsupporting
confidence: 68%
“…In agreement with our initial correlative analyses, we found in LoLiNuts pro-inflammatory cytokines like IL-6, IL-8, and G-SCF and the damage parameter CK to be increased at the early stages of trauma (at 0–3 h IL-6, IL-8, and G-CSF, at 24 h IL-8 and at 48 h CK), implying that high levels of these cytokines at early time points after trauma are linked to a low ANSP score in the 48 h to 120 h interval. Macrophage-derived chemokine (MDC), which is a ligand for CCR4 and has been already implemented as a mediator of lung inflammation upon trauma (27) while being on average elevated at the 120 h time-point (Fig. 3), was the only factor of all the mediators analyzed that presented with a higher concentration at the 120 h time-point in HiLiNuts.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the previous study in adults 25 , 27 , we found that relative abundance of Prevotella was indirectly associated with peripheral CD4 count and directly associated with MDC in perinatally HIV-infected children. MDC has emerged as novel modulator of lung inflammation in mice 48 and an inflammatory marker to assess the severity of atopic dermatitis in children and infants 49 . More recently, the increased levels of MDC in HIV-infected adults have also been reported 50 .…”
Section: Discussionmentioning
confidence: 99%